Triggering of microearthquakes in Iceland by volatiles released from a dyke intrusion - Martens, H. R.; White, R. S. (Geophysical Journal International, 2013)
We suggest that carbon dioxide exsolved from a mid-crustal basaltic dyke intrusion in Iceland migrated upwards and triggered shallow seismicity by allowing failure on pre-existing fractures under the relatively low elastic stresses (100–200 kPa; 1–2 bar) generated by the dyke inflation. Intense swarms of microseismicity accompanied magmatic intrusion into a dyke at depths of 13–19 km in the crust of Iceland's Northern Volcanic Rift Zone during 2007–2008. Contemporaneously, a series of small normal earthquakes, probably triggered by elastic stresses imposed by the dyke intrusion, occurred in the uppermost 4 km of crust: fault plane solutions from these are consistent with failure along the extensional fabric and surface fissure directions mapped in the area, suggesting that the faults failed along existing rift zone fabric even though the mid-crustal dyke is highly oblique to it. Several months after the melt froze in the mid-crust and seismicity associated with the intrusion had ceased, an upsurge in shallow microseismicity began in the updip projection of the dyke near the brittle–ductile transition at 6–7 km depth below sea level. This seismicity is caused by failure on right-lateral strike-slip faults, with fault planes orientated 23 ± 3°, which are identical with the 24 ± 2° orientation in this area of surface fractures and fissures caused by plate spreading and extension of the volcanic rift zone. However, these earthquakes have T-axes approximately aligned with the opening direction of the dyke, and the right-lateral sense of failure is opposite that of regional strike-slip faults. We suggest that the fractures occurred along pre-existing weaknesses generated by the pervasive fabric of the rift zone, but that the dyke opening in the mid-crust beneath it caused right-lateral failure. The seismicity commenced after a temporal delay of several months and has persisted for over 3 yr. We propose that fluids exsolved from the magma in the dyke, primarily carbon dioxide, percolated updip and to shallower depths predominantly along pre-existing fractures. Increased pore pressure from the volatiles reduced the effective normal compressive stress on faults, increasing the likelihood of failure and allowing the modest stress changes generated by the intrusion to cause failure. Propagation of volatiles through the crust would also account for the observed time delay between the intrusion at depth and the shallow earthquake clusters. A further short-lived cluster of earthquakes at 2–4 km depth beneath the surface exhibits left-lateral strike-slip faulting with epicentres well orientated along a lineation which is identical with other subparallel strike-slip faults in the area that transfer motion between two adjacent spreading segments. These shallow earthquakes lie beyond lobes of significant positive Coulomb stress change caused by the intrusion, implying minimal modifications to the stress field in their vicinity; hence, they continue to respond to the regional stress field rather than the local stress field generated by the dyke intrusion.